Resiprositas Dalam Ritual Tradisi Sedekah Bedusun Di Desa Kartamulia Kecamatan Gelumbang Kabupaten Muara Enim - Fitriah , Ayu Wardatul; Suryati, Suryati; Muzaiyanah, Muzaiyanah (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This study discusses "Reciprocity in the Ritual of the Bedusa Alms Tradition in Kartamulia Village, Gelumbang District, Muara Enim Regency". The purpose of this study was to find out about the factors, impacts and obstacles of the alms bedusun tradition in Kartamulia Village, Gelumbang District, Muara Enim Regency. The traditional alms bedusun ritual is a tradition that is carried out with the aim of praying for the spirits of ancestors, deceased families and the safety of the village. This research is included in the category of qualitative research which is a field research (field research), the data collection tools used are interviews, observation, and documentation. The subjects of this study were five fathers of the Kartamulia Village community. The data analysis technique used is data reduction, data presentation and conclusion. The results of this study are 1) Factors, the process of the tradition of giving alms bedusun is in the form of positive factors that establish close family relationships, lead a community on the path to peace and tranquility, besides that it makes the community directly interact well with one another. The process of the bedusun alms tradition has 3 stages, namely the preparatory stage, the implementation stage, the final stage. 2) The impact and obstacle of the reciprocity of the bedusun alms tradition is the impact of reciprocity, which is a reciprocal exchange for which the community gets gratitude, and shares, and is mutually beneficial. And there are no obstacles because the almsgiving at the bedusun is a custom and has been carried out from our ancestors. 3) this bedusun alms tradition is carried out so that the community still preserves the custom and to know that there is a mutually beneficial impact on the community. Kartamulia Village, Gelumbang District, Muara Enim Regency established good friendly relations between residents of other Kartamulia Villages.